THE ROLE OF DAYAH DARUL AMIN AL-WAALIYAH IN THE DEVELOPMENT OF COMMUNITY RELIGION - Helmiati, Helmiati (Jurnal Ilmiah Pendidikan Anak (JIPA), 2019)
This study aims to determine how the role, what methods are used as well as obstacles and solutions of Dayah Darul Amin Al-Waaliyah in fostering community religion in Ilie Village. The research population was all the people in the village of Ulee Kareng Sub-District, Banda Aceh City, which were as many as 625 households using random sampling techniques. Data collection was carried out using test, questionnaire and documentation techniques. The results of the study show that Dayah as a center for da'wah and social empowerment that is very important in broadcasting Dayah religion fostering/forming generations of cadres so that young generation cadres have good/perfect morals and more so that they are firm in their faith in Allah, because they are more directed 'ubudiah to Allah swt. This finding is expected to be used by leader of Dayah Darul Amin Al-Waaliyah in growing public awareness of religion, developing and implementing study methods and being able to overcome any obstacles by deliberating.Â Keywords: Role of dayah; Religious formation